2012
DOI: 10.1089/aid.2011.0145
|View full text |Cite
|
Sign up to set email alerts
|

Massive CD8 T Cell Response to Primary HIV Infection in the Setting of Severe Clinical Presentation

Abstract: Acute HIV-1 infection causes a rapid total body depletion of CD4 + T cells in most individuals and HIV-1-specific CD8 + T cell expansion in response to viral replication. A numerically high CD8 T cell response may indicate limited T cell repertoire against HIV and rapid progression. We present a detailed evaluation of an acutely infected individual with a strong HIV-1-specific CD8 T cell response targeting multiple epitopes demonstrating that the upper limit of CD8 expansion in this setting may be much higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The current Research Topic includes in total 11 high-quality manuscripts, ranging from host-response activation during HIV infection (Tjitro et al While it is known that HIV infection is characterized by a dramatic depletion of CD4 + T cells, a study comparing people with HIV (PWH) with age-matched uninfected controls identified specifically gamma delta (γδ)-T cells as an inflammatory driver in ART-suppressed PWH and provided evidence of distinct "inflamm-aging" processes with and without active HIV replication (Belkina et al). Depletion of CD4 + T cells together with impaired polarization of Th17 cells in the gastrointestinal tract and a massive expansion of activated CD8 + T cells causes CD8 + T cell-mediated enteropathy (6). In another study of this Research Topic authors also reported dysbiosis and translocation of microbial products in the study participants, which persisted despite long term ART mediated viral suppression (Rhoades et al).…”
Section: Hiv-associated Immune Activation and Persistent Inflammationmentioning
confidence: 95%
“…The current Research Topic includes in total 11 high-quality manuscripts, ranging from host-response activation during HIV infection (Tjitro et al While it is known that HIV infection is characterized by a dramatic depletion of CD4 + T cells, a study comparing people with HIV (PWH) with age-matched uninfected controls identified specifically gamma delta (γδ)-T cells as an inflammatory driver in ART-suppressed PWH and provided evidence of distinct "inflamm-aging" processes with and without active HIV replication (Belkina et al). Depletion of CD4 + T cells together with impaired polarization of Th17 cells in the gastrointestinal tract and a massive expansion of activated CD8 + T cells causes CD8 + T cell-mediated enteropathy (6). In another study of this Research Topic authors also reported dysbiosis and translocation of microbial products in the study participants, which persisted despite long term ART mediated viral suppression (Rhoades et al).…”
Section: Hiv-associated Immune Activation and Persistent Inflammationmentioning
confidence: 95%
“…Studies in the simian immunodeficiency virus (SIV) model suggested that viral load decline after ART initiation during chronic SIV infection was independent from CD8 + T cell-mediated killing of SIVinfected cells (13,14). HIV-specific CD8 + T cells are induced at the early stage of infection at high numbers, and the magnitude and survival capacity of these responses in acute infection have been associated with a lower viral load set point (15)(16)(17)(18). Although the emergence of HIV-specific CD8 + T cells has been temporally associated with viral load decline in the absence of treatment (5,7,8), no study has yet reported a direct correlation between these responses and viral load decline.…”
Section: Introductionmentioning
confidence: 99%
“…CD4 + T cells trigger many elements of the immune response, including regulation of CD8 + T cell activation ( 1 ). Early HIV infection is characterized by a dramatic depletion of CD4 + T cells and impaired polarization of Th17 cells in the gastrointestinal tract and a massive expansion of activated CD8 + T cells causing CD8 + T cell-mediated enteropathy ( 2 4 ), which is also characterized by microbial overgrowth and translocation of microbial products, including bacteria, fungi, and viruses, from the gut into the systemic circulation ( 5 ). Lactobacillales influence gut mucosal immunity by increasing the suppressive function of CD4 + regulatory T cells of colon lamina propria, which can alleviate HIV-associated colitis ( 1 ).…”
Section: Introductionmentioning
confidence: 99%